ORGANIZATIONAL CULTURE AS A MODERATOR BETWEEN PATERNALISTIC LEADERSHIP STYLE AND ORGANIZATIONAL COMMITMENT: A CASE OF BANKING SECTOR, IRAQ (World Economics and Finance Bulletin, 2022)
This study seeks to examine the mediating role of organizational culture between the patriarchal leadership style and organizational commitment in the banking framework. This is an interpretive study based on 345 employees working in two private banks located in southern Iraq. Bank of Baghdad and Al Janoob Islamic Bank using a stratified sampling technique. Data were collected using the organizational commitment scale, the parental leadership scale, and the organizational culture scale. Descriptive statistics, reliability analysis, Pearson correlation and hypothesis testing using multiple hierarchical regression were used. The results indicate that the paternalistic leadership style closely related to organizational commitment and organizational culture acted as the mediator in this relationship. The study also indicated the positive relationship between patriarchal leadership style, organizational culture, organizational commitment and organizational culture.
Keywords: Paternalistic Leadership; Organizational Culture; Organizational Commitment.